PEMBELAJARAN MULTI REPRESENTASI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMA PADA METERI HUKUM II NEWTON - Sari, Ambar (Universitas Muhammadiyah Ponorogo, 2023)
The aim of this research is determine the extent to which learning using multiple representations is able to improve students' problem solving abilities in Newton's Second Law. The research subjects consisted of 24 students of class X 1 Senior High School 8 Malang. This research uses an instrument in the form of an integrated concept mastery test with problem solving abilities consisting of 6 multiple choice questions accompanied by reasons, an interview guide and a problem solving observation sheet. The approach to this research is mixed methods with an embedded experimental model design. The research results show that using multiple representations can increase students' problem solving abilities from an average of 1.1 approaching level 1 (inadequate) to 2.2 approaching level 2 (need some improvement). Learning with multiple representations can also change students from novice behavior to experts in problem solving Newton's Second Law